2011
DOI: 10.1186/1476-511x-10-238
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Brown Adipose Tissue Activity and Neoplastic Status: an 18F-FDG PET/CT Study in the Tropics

Abstract: BackgroundBrown adipose tissue (BAT) has thermogenic potential. For its activation, cold exposure is considered a critical factor though other determinants have also been reported. The purpose of this study was to assess the relationship between neoplastic status and BAT activity by 2-deoxy-2-[18F]fluoro-D-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in people living in the tropics, where the influence of outdoor temperature was low.Methods18F-FDG PET/CT scans were reviewed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…Human brown fat is composed of adipocytes similar to both classical interscapular brown adipocytes (Cypess et al, 2013;Jespersen et al, 2013;Lidell et al, 2013) and mouse white adipocytes converted into brown (Sharp et al, 2012;Wu et al, 2012). Moreover, a recent imaging study showed increased metabolic activity of BAT in PET-CTs of cancer patients (Huang et al, 2011). We have shown a switch from white to brown adipocytes in WAT of mice with CAC.…”
Section: Discussionmentioning
confidence: 52%
“…Human brown fat is composed of adipocytes similar to both classical interscapular brown adipocytes (Cypess et al, 2013;Jespersen et al, 2013;Lidell et al, 2013) and mouse white adipocytes converted into brown (Sharp et al, 2012;Wu et al, 2012). Moreover, a recent imaging study showed increased metabolic activity of BAT in PET-CTs of cancer patients (Huang et al, 2011). We have shown a switch from white to brown adipocytes in WAT of mice with CAC.…”
Section: Discussionmentioning
confidence: 52%
“…However, in patients living in tropical areas where the consistently warm outdoor temperature and the limited day length variation reduce the effect of cold environment and length of day on BAT, neoplastic status, more than temperature and day length, is a critical determinant of BAT activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…74 In another study, BAT activity was measured via 18 F-fluorodeoxylucose positron-emission tomography/computed tomography (FDG PET/CT) in human patients with cancer and was found to correlate positively with cancer stage. 78 However, classical BAT is relatively limited in mass, localized to relatively small depots within the body, therefore severely limiting its capacity to offer substantial contributions to energy expenditure and CAC in humans. 79,80 More studies are needed to provide a quantitative assessment of classical BAT's contributions to CAC.…”
Section: Brown and Beige Adipose Tissue Expansion And Activationmentioning
confidence: 99%